PENGARUH KECERDASAN EMOSIONAL, KARAKTERISTIK PEKERJAAN DAN KOMUNIKASI KERJA TERHADAP KINERJA PEGAWAI DI DINAS KESEHATAN PEMERINTAH KABUPATEN LABUHANBATU - Sri Junerti; Tengku Aisyah Azra; Harjono Sanito; Thariq Bin Zaid At Taufiq; Deny Siregar (Universitas Islam Islam Sumatera Utara, 2021)
Based on initial observations made by researchers, it was found that several problems became the background of this research, namely: the low concern of employees in listening to other people's problems in order to support smooth work. The lack of openness, empathy and support among co-workers. Employee awareness is still low in controlling the completion of the work they carry out. And communication between superiors and subordinates is still formal, which results in information, ideas and suggestions from subordinates not reaching their superiors. The formulation of the problem in this study is whether the influence of emotional intelligence on employee performance. What is the effect of job characteristics on employee performance? What is the effect of work communication on employee performance? What is the effect of emotional intelligence, job characteristics and work communication on employee performance at the Labuhanbatu District Government Health Office. The purpose of this study was to determine and analyze the effect of emotional intelligence on employee performance. The effect of job characteristics on employee performance. The effect of work communication on employee performance. As well as the influence of emotional intelligence, job characteristics and work communication on employee performance simultaneously at the Labuhanbatu District Government Health Office. The sample in this study amounted to 88 people. The data analysis technique used in this research is descriptive analysis and multiple linear regression analysis. The results of this study explain that the variables of emotional intelligence and work communication have a significant effect on employee performance. While the job characteristics variable has no significant effect on employee performance. Simultaneously, the variables of emotional intelligence, job characteristics and work communication have a positive and significant effect on employee performance at the Labuhanbatu District Health Office.